Mobile Learning Design Theories and Application - Churchill, Daniel; Lu, Jie; Chiu, Thomas K.F; Fox, Bob (Lecture Notes in Educational Technology, 2016)
This book focuses on mobile learning design from both theoretical and practical perspectives. It introduces and discusses how mobile learning can be effectively integrated into curricula, highlighting the design of four key components of learning-centric pedagogy: Resource, Activity, Support and Evaluation in the context of mobile learning. It also investigates the learning theories underpinning mobile learning design, and includes case studies in different contexts. It provides practical insights that allow teachers to change and transform teaching practices using mobile technology. Anyone involved in mobile-technology enhanced learning and teaching will find this book both informative and useful.